Apixaban vs. warfarin in patients with left ventricular thrombus: a prospective multicentre randomized clinical trial. Issue 7 (19th July 2021) - Alcalai, Ronny; Butnaru, Adi; Moravsky, Gil; Yagel, Oren; Rashad, Razek; Ibrahimli, Mahsati; Planer, David; Amir, Offer; Elbaz-Greener, Gabby; Leibowitz, David
Abstract: Aims: Current guidelines recommend anticoagulation with a vitamin K antagonist to treat left ventricular (LV) thrombus after myocardial infarction (MI). Data on the use of direct oral anticoagulants (DOACs) in this setting are limited. The aim of the study was to assess the efficacy of apixaban vs. warfarin in treating LV thrombus after MI. Methods and results: We conducted a prospective, randomized, multicentre open-label clinical trial including patients with LV thrombus detected by 2D transthoracic echocardiography 1–14 days after acute MI. Thirty-five patients were enrolled in three medical centres; 17 patients were randomized to warfarin and 18 patients to apixaban. The primary outcome was the presence and size of LV thrombus 3 months after initiation of anticoagulation. Secondary outcomes were major bleeding, stroke or systemic embolism, re-hospitalization, and all-cause mortality. Mean LV thrombus size at enrolment was 18.5 mm × 12.3 mm in the warfarin group and 19.9 mm × 12.4 mm in the apixaban group ( P  = NS). Thirty-two patients completed 3 months follow-up. In the warfarin group, two patients withdrew, and in the apixaban group one patient died. Thrombus completely resolved in 14 of 15 patients in the warfarin group and in 16 of 17 patients in the apixaban group ( P  = NS and P  = 0.026 for non-inferiority). Two patients had major bleeding in the warfarin group, while no major bleeding events were recorded in the apixaban group. There was one stroke in the warfarin group and one death in the apixaban group. Conclusion: Our results suggest that apixaban is non-inferior to warfarin for treatment of patients with LV thrombus after acute MI with a 20% non-inferiority margin.